Effects of constant temperature and daily fluctuating temperature on the transovarial transmission and life cycle of Aedes albopictus infected with Zika virus - Jian, Xian-yi; Jiang, Yu-ting; Wang, Miao; Jia, Nan; Cai, Tong; Xing, Dan; Li, Chun-xiao; Zhao, Tong-yan; Guo, Xiao-xia; Wu, Jia-hong (Frontiers in Microbiology, 2023)
Numerous studies on mosquito life cycle and transmission efficacy were performed under constant temperature. Mosquito in wild, however, is not exposed to constant temperature but faced with temperature variation on a daily basis. In the present study, the mosquito life cycle and Zika virus transmission efficiency were conducted at daily fluctuating temperature and constant temperatures. Aedes albopictus was infected with Zika virus orally. The oviposition and survival of the infected mosquitoes and hatching rate, the growth cycle of larvae at each stage, and the infection rate of the progeny mosquitoes were performed at two constant temperatures (23℃ and 31℃) and a daily fluctuating temperature (23~31℃). Under the condition of daily fluctuation temperature, the survival rate of Ae. Albopictus, the number of eggs laid and hatching rate were significantly higher than that of constant temperature. However, growth, development and fecundity of progeny mosquitoes under fluctuating temperatures were significantly lower than constant temperatures. The extrinsic incubation temperature has no effect on transovarial transmission. The results show that there are significant differences between mosquito development and reproductive cycles under fluctuating and constant temperature conditions and fluctuating temperature is more favorable for mosquitoes’ survival and reproduction. The data would support mapping and predicting the distribution of Aedes mosquitoes in the future and establishing an early warning system for Zika virus epidemics.